The Effect of Liquidity, Capital Adequacy, Operational Risk, and Credit Risk on Profitability: A Study on Banks Listed on the Indonesia Stock Exchange - Komang Karina Pramesti; I Gde Kajeng Baskara (Digital Innovation : International Journal of Management, 2025)
Profitability represents a bank's capability to evaluate how effectively its management generates profits. This study seeks to explore and determine the influence of liquidity, capital adequacy, operational risk, and credit risk on bank profitability. The research focuses on banking institutions listed on the Indonesia Stock Exchange over the 2021–2023 period. The study utilizes quantitative data obtained from secondary sources, specifically financial statements published by the respective banks. A total of 32 banks were selected as research samples through purposive sampling. The study adopts a non-participant observation approach, and the data were processed using multiple linear regression analysis. The results indicate that liquidity has a positive yet statistically insignificant effect on profitability, capital adequacy has a significant negative effect, operational risk shows a negative but non-significant influence, and credit risk has a significant negative impact on bank profitability.